Simultaneous abatement of diesel soot and NOX emissions by effective catalysts at low temperature: An overview. Issue 3 (3rd July 2018) - Dhal, Ganesh Chandra; Dey, Subhashish; Mohan, Devendra; Prasad, Ram
ABSTRACT: The diesel engine generally achieves the highest fuel, energy, and thermal efficiency due to its very high compression/expansion ratio (14:1 to 25:1). Diesel engines can have a thermal efficiency that exceeds 50%. The main problem is that they emit more pollution like fine black soot particulates (C8 H to C10 H) and nitrogen oxides (NO X ). These pollutants have been causing serious problems for human health and the global environment and also impacts on the engine. There are many types of catalysts investigated for simultaneous control of these two pollutants, i.e., platinum group metals (PGM; Pt, Pd, Rh, and Ir) based, spinel-type oxides, hydrotalcite, rare earth metal oxides, mixed transient metal oxides, etc. The high raw material cost of PGM catalysts has become a significant issue, so developing non-PGM catalysts are one of the promising challenges. There are no extra reductants required because soot catalytically oxidizes itself in the presence of NO X at a faster rate than molecular oxygen and simultaneously NO X is reduced to nitrogen. The order of oxidation potential of NO X to oxidized soot in comparison to molecular oxygen is as follows: NO2  > NO > O2 . To meet the very strict EPA US 2010 and Euro VI regulations of particulate matter (PM) and NO X for heavy-duty and light-duty vehicular stringent emission, it is very important to apply the integrated catalytic systems to significantly remove PM and NO X simultaneously. Many papers related to simultaneous control of soot and NO X over different catalysts have been published but till now some of effective catalysts showing high conversion at low temperatures (possibly within the range typical of diesel exhaust: 150–450°C) have not been reviewed. Thus, this article provides a summary of published information regarding the effective catalysts, their preparation methods, properties, and application for simultaneous control of diesel soot and NO X .